Program pembiasaan mushofahah terhadap guru untuk meningkatkan kualitas adab siswa MA Al-Hidayah Citaringgul - Parhan, Ahmad; Subagiya, Bahrum (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
The mushofahah habituation program is a very effective method in improving the quality of student manners at MA Al-Hidayah Citaringgul. Mushofahah, which is a tradition of shaking hands while praying for each other, teaches students about the importance of respect, politeness, and fostering harmonious relationships between students and teachers. Through mushofahah, students learn to appreciate the role of teachers as educators and leaders in schools. This study aims to describe and critically analyze the mushofahah program in improving student manners. A qualitative approach with a case study method was used, involving all students and teachers. Data were collected through interviews, observations, questionnaires, and documentation. Qualitative descriptive analysis includes four aspects: understanding and perception, participation, impact, and evaluation of the mushofahah program. The results showed that this program had a significant influence in shaping student manners, especially in respectful attitudes and better interactions between students and teachers. Abstrak Program pembiasaan mushofahah merupakan metode yang sangat efektif dalam meningkatkan kualitas adab siswa di MA Al-Hidayah Citaringgul. Mushofahah, yaitu tradisi berjabat tangan sambil saling mendoakan, mengajarkan siswa tentang pentingnya rasa hormat, kesopanan, serta membina hubungan yang harmonis antara siswa dan guru. Melalui mushofahah, siswa belajar menghargai peran guru sebagai pendidik dan pemimpin di sekolah. Penelitian ini bertujuan mendeskripsikan dan menganalisis secara kritis program mushofahah dalam meningkatkan adab siswa. Pendekatan kualitatif dengan metode studi kasus digunakan, melibatkan seluruh siswa dan guru. Data dikumpulkan melalui wawancara, observasi, kuesioner, dan dokumentasi. Analisis deskriptif kualitatif mencakup empat aspek: pemahaman dan persepsi, partisipasi, dampak, serta evaluasi program mushofahah. Hasil penelitian menunjukkan bahwa program ini memiliki pengaruh signifikan dalam membentuk adab siswa, khususnya dalam sikap hormat dan interaksi yang lebih baik antara siswa dan guru.